RecA tests homology at both pairing and strand exchange - Bazemore, L. Rochelle (The National Academy of Sciences of the USA, 1997)
RecA is a 38-kDa protein from Escherichia coli that polymerizes on single-stranded DNA, forming a nucleoprotein filament that pairs with homologous duplex DNA and carries out strand exchange in vitro. To observe the effects of mismatches on the kinetics of the RecA-catalyzed recombination reaction, we used assays based upon fluorescence energy transfer that can differentiate between the pairing and strand displacement phases. Oligonucleotide sequences that produced 2–14% mismatches in the heteroduplex product of strand exchange were tested, as well as completely homologous and heterologous sequences. The equilibrium constant for pairing decreased as the number of mismatches increased, which appeared to result from both a decrease in the rate of formation and an increase in the rate of dissociation of the intermediates. In addition, the rate of strand displacement decreased with increasing numbers of mismatches, roughly in proportion to the number of mismatches. The equilibrium constant for pairing and the rate constant for strand displacement both decreased 6-fold as the heterology increased to 14%. These results suggest that discrimination of homology from heterology occurs during both pairing and strand exchange.